2016
DOI: 10.1007/s12011-016-0662-y
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Boric Acid Used to Treat Experimental Osteomyelitis Caused by Methicillin-Resistant Staphylococcus aureus: an In Vivo Study

Abstract: We explored the ability of local and systemic applications of boric acid (BA) to reduce the numbers of methicillin-resistant Staphylococcus aureus (MRSA) in a rat model of tibial osteomyelitis (OM), and compared boric acid with vancomycin (V). Implant-associated osteomyelitis was established in 35 rats. After 4 weeks, at which time OM was evident both radiologically and serologically in all animals, the rats were divided into five groups of equal number: group 1, control group (no local application of BA or ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
13
0
2
Order By: Relevance
“…Inflammation is associated with bacterial infection. Previous studies showed that increased inflammation is associated with osteomyelitis (Yoshii et al, 2002 ; Lew and Waldvogel, 2004 ; Guzel et al, 2016 ). Despite of its lacking antimicrobial function in MRSA induced osteomyelitis, we did observe a significant reduction of pro-inflammatory cytokines in rats treated with erythromycin alone.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Inflammation is associated with bacterial infection. Previous studies showed that increased inflammation is associated with osteomyelitis (Yoshii et al, 2002 ; Lew and Waldvogel, 2004 ; Guzel et al, 2016 ). Despite of its lacking antimicrobial function in MRSA induced osteomyelitis, we did observe a significant reduction of pro-inflammatory cytokines in rats treated with erythromycin alone.…”
Section: Discussionmentioning
confidence: 95%
“…In the current study, we successfully established chronic implant-induced osteomyelitis in male Wistar rats as described previously (Lucke et al, 2003 ; Vergidis et al, 2015 ; Guzel et al, 2016 ). Using this model, we studied the effects of erythromycin alone, curcumin alone and erythromycin and curcumin combined treatment against MRSA induced osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum score of one tibia including four examined regions and four mentioned parameters was 24 for each animal as previously described. 28…”
Section: Assessment Of Induced Osteomyelitis By Histopathological Anamentioning
confidence: 99%